Direct Shear Strength Properties of Limestone-Blended Embankment Materials - Jonathan R. Dungca (IPTEK Journal of Proceedings Series, 2017)
The vast distribution of limestone in the Philippines makes limestone quarrying prevalent resulting to the accumulation of waste limestone. This opened the idea of utilizing the wastes as embankment materials which would result to a more economical construction. In order to test the ability of limestone to be an embankment material, its strength and consolidation parameters are evaluated in different mixed proportions, at 0%, 20%, 40%, 60% and 100%, with the conventional embankment material using the direct shear test. Index properties (i.e. specific gravity, Atterberg limits, and maximum and minimum index densities) were obtained for all the blends in order to produce empirical relationships with the different percentage of limestone. It was found out that the cohesion increased with the addition of limestone, although there was a decrease in the internal angle of friction.